Analisis Kreativitas Ilmiah Mahasiswa pada Mata Kuliah Farmakognosi Berbasis Praktikum - Sri Idawati; Aliefman Hakim; Agus Abhi Purwoko; Wahab Jufri; Joni Rokhmat; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2025)
Scientific creativity is an important competency in Higher Education, especially in the fields of science and technology. This research aims to analyze the level of scientific creativity of D-III Pharmacy students in practicum-based Pharmacognosy courses. In Torrance's indicators, there are four indicators used to measure the level of scientific creativity of students, namely fluency, flexibility, originality, and elaboration. The research method used is quantitative descriptive method with data collection through observation, and questionnaire forms. The research subjects were 3rd semester (odd) pharmacy D-III study program students with a total of 30 students. The results showed that the level of scientific creativity of students tended to be in the less category. As for the level of student creativity in each Torrance indicator, namely fluency is in the medium category (51%), originality is in the less category (23%), flexibility is in the less category (25%), and elaboration is in the less category (26%).